Implications of refined altimetry on estimates of mesoscale activity and eddy‐driven offshore transport in the Eastern Boundary Upwelling Systems. Issue 21 (10th November 2014) - Capet, Arthur; Mason, Evan; Rossi, Vincent; Troupin, Charles; Faugère, Yannice; Pujol, Isabelle; Pascual, Ananda
Abstract We investigate the extent to which the recently upgraded version of the Ssalto/Duacs sea level anomaly product affects the description of mesoscale activity in the Eastern Boundary Upwelling Systems (EBUS). Drifter observations confirm that the new data set released by Archiving, Validation and Interpretation of Satellite Oceanographic data (AVISO) in April 2014 (DT14) offers an enhanced description of mesoscale activity for the four EBUS. DT14 returns significantly higher eddy kinetic energy levels (+80%) within a 300 km coastal band, where mesoscale structures are known to induce important lateral physical and biogeochemical fluxes. When applied to DT14, an automatic eddy detection algorithm detects more eddies in the EBUS (+37%), and lower eddy radius estimates, in comparison with results using the former altimetry product (DT10). We show that despite higher eddy densities, the smaller eddy radii result in westward eddy transport estimates that are smaller than those obtained from DT10 (−12%).